2016
DOI: 10.1016/j.jval.2016.03.1179
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Hiv Stigma as a Barrier to Sustained Art Adherence in North West Ethiopia: A Cohort Study

Abstract: Objectives: Colorado has the lowest rate of measles vaccination in the entire country, partially due to the ease of obtaining non-medical exemptions. Our primary objective was to determine the magnitude and cost of a measles outbreak in Denver at current vaccination coverage levels. We then simulated the effect of changing the Colorado non-medical exemption complexity to medium or difficult. MethOds: An agent based transmission model simulated the transmission of the measles virus in Denver following the intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Those who experience stigma in a healthcare setting are also less likely to initiate antiretroviral therapy [25]. Available cohort data suggests that perceived stigma is associated with poor medication adherence according to participant reports and chart reviews [5355]. A longitudinal cohort study of adults living with HIV in South Africa revealed that internalized stigma was associated with a greater incidence of condomless sex with both HIV-negative/unknown and HIV-positive partners [5].…”
Section: Resultsmentioning
confidence: 99%
“…Those who experience stigma in a healthcare setting are also less likely to initiate antiretroviral therapy [25]. Available cohort data suggests that perceived stigma is associated with poor medication adherence according to participant reports and chart reviews [5355]. A longitudinal cohort study of adults living with HIV in South Africa revealed that internalized stigma was associated with a greater incidence of condomless sex with both HIV-negative/unknown and HIV-positive partners [5].…”
Section: Resultsmentioning
confidence: 99%
“…MSM, SW, PWID, those with mental health or other substance use disorders, etc. ), stigma remains a barrier to HIV care, contributing to delays in ART initiation . Men, particularly, are not adequately served by traditional approaches, as they remain less likely than women to start ART and they have more advanced disease than women when they start ART .…”
Section: Resultsmentioning
confidence: 99%
“…Late ART initiation has persisted and is preventing more rapid declines in HIV mortality and incidence in the region. Importantly, men, those experiencing multiple dimensions of stigma, and other underserved populations are being left behind as HIV treatment expands in SSA . New age and sex‐disaggregated metrics and targeted strategies for earlier diagnosis (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian Yang et al, (2020) menunjukkan hasil skor rata-rata stigma berdasarkan Berger HIV Stigma Scale adalah 105.13 (stigma tingkat sedang). Erku et al, (2016) dalam penelitiannya didapatkan bahwa dalam pelaksanaan untuk mengurangi stigma pada penderita HIV positif atau ODHA, dalam pelaksanaanya dapat melakukan berbagai faktor yang dapat mempengaruhi, seperti dukungan orang tua atau orang terdekat dan dukungan masyarakat untuk meningkatkan kepatuhan dalam terapi ARV yang lebih baik.…”
Section: Pendahuluanunclassified